Ecdysteroidogenesis and development in Heliothis virescens (Lepidoptera: Noctuidae): Focus on PTTH-stimulated pathways. (May 2018) - Scieuzo, Carmen; Nardiello, Marisa; Salvia, Rosanna; Pezzi, Marco; Chicca, Milvia; Leis, Marilena; Bufo, Sabino A.; Vinson, S. Bradleigh; Rao, Asha; Vogel, Heiko; Falabella, Patrizia
Graphical abstract: Highlights: MAPK and PI3K pathways are involved in Heliothis virescens ecdysteroidogenesis. Proteins of MAPK and PI3K pathways are conserved in phylogenetically distant species. TOR pathway is involved in growth and development of Heliothis virescens . TOR pathway has a specific role in ecdysteroidogenesis of Heliothis virescens . Abstract: Post-embryonic development and molting in insects are regulated by endocrine changes, including prothoracicotropic hormone (PTTH)-stimulated ecdysone secretion by the prothoracic glands (PGs). In Lepidoptera, two pathways are potentially involved in PTTH-stimulated ecdysteroidogenesis, mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/protein kinase B/target of rapamycin (PI3K/Akt/TOR). We investigated the potential roles of both these pathways in Heliothis virescens ecdysteroidogenesis. We identified putative proteins belonging to MAPK and PI3K/Akt/TOR signaling cascades, using transcriptomic analyses of PGs from last (fifth) instar larvae. Using western blots, we measured the phosphorylation of 4E-BP and S6K proteins, the main targets of TOR, following the in vitro exposure of PGs to brain extract containing PTTH (hereafter referred to as PTTH) and/or the inhibitors of MAPK (U0126), PI3K (LY294002) or TOR (rapamycin). Next, we measured ecdysone production, under the same experimental conditions, by enzyme immunoassay (EIA). We found that in Heliothis virescens last instar larvae, both pathways modulated PTTH-stimulated ecdysteroidogenesis. Finally, we analyzed the post-embryonic development of third and fourth instar larvae fed on diet supplemented with rapamycin, in order to better understand the role of the TOR pathway in larval growth. When rapamycin was added to the diet of larvae, the onset of molting was delayed, the growth rate was reduced and abnormally small larvae/pupae with high mortality rates resulted. In larvae fed on diet supplemented with rapamycin, the growth of PGs was suppressed, and ecdysone production and secretion were inhibited. Overall, the in vivo and in vitro results demonstrated that, similarly to Bombyx mori, MAPK and PI3K/Akt/TOR pathways are involved in PTTH signaling-stimulated ecdysteroidogenesis, and indicated the important role of TOR protein in H. virescens systemic growth.